DMBT1 expression and neutrophil-to-lymphocyte ratio during necrotizing enterocolitis are influenced by impaired perfusion due to cardiac anomalies. - Diez, Sonja; Besendörfer, Manuel; Weyerer, Veronika; Hartmann, Arndt; Moosmann, Julia; Weiss, Christel; Renner, Marcus; Müller, Hanna (Molecular and Cellular Pediatrics, 2022)
BACKGROUND: Deleted in malignant brain tumors 1 (DMBT1) is involved in innate immunity and epithelial differentiation. It has been proven to play a role in various states of inflammation or hypoxia of fetal gastrointestinal and pulmonary diseases. Discrimination of pathogenesis in necrotizing enterocolitis (NEC) based on cardiac status improves the understanding of NEC in different patient subgroups. We aimed at examining DMBT1 expressions regarding their association with cardiac status leading to impaired intestinal perfusion, intraoperative bacteria proof, and a fulminant course of NEC. METHODS: Twenty-eight patients with NEC were treated surgically between 2010 and 2019 at our institution. DMBT1 expression was examined in intestinal sections using immunohistochemistry to detect DMBT1 protein. Associations of clinical parameters and DMBT1 expression were analyzed. RESULTS: We examined DMBT1 levels in 10 patients without cardiac defects and 18 patients with persisting ductus arteriosus (PDA) and congenital heart defects (CHD). Compared to patients without cardiac malformations, DMBT1 levels tended to score higher in patients with PDA/CHD (p = 0.2113) and were negatively correlated with C-reactive protein in these infants (p = 0.0172; r = - 0.5533). The number of DMBT1-expressing macrophages was elevated in the PDA/CHD-subgroup (p = 0.0399). Ratios of neutrophils and monocytes to lymphocytes were significantly higher in infants with PDA/CHD (p = 0.0319 and 0.0493). DMBT1 expression was significantly associated with positive bacterial culture of intraoperative swabs (p = 0.0252) and DMBT1 expression of the serosa was associated with a fulminant course of NEC (p = 0.0239). CONCLUSIONS: This study demonstrates that DMBT1 expression may be influenced by cardiac anomalies with an impaired intestinal perfusion in the neonatal intestine. NEC in PDA/CHD infants is associated with more DMBT1-positive macrophages and a significantly elevated neutrophil-to-lymphocyte ratio.
EVALuna2:497662
Keywords: DMBT1; Deleted in malignant brain tumors 1; Necrotizing enterocolitis; Congenital heart disease; Neutrophil-to-lymphocyte ratio; Monocyte-to-lymphocyte ratio